Widening and Deepening: Reforming the European Union - Berglof, Erik; Burkart, Mike; Friebel, Guido; Paltseva, Elena (American Economic Review, 2008)
Widening and Deepening: Reforming the European Union by Erik Berglof, Mike Burkart, Guido Friebel and Elena Paltseva. Published in volume 98, issue 2, pages 133-37 of American Economic Review, May 2008